Pengaruh Kinerja Keuangan terhadap Pertumbuhan Nilai Pasar Perusahaan pada Sektor Teknologi di BEI - Putri Nola Munthe (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of financial ratios on the growth of market value of technology sector companies listed on the Indonesia Stock Exchange (IDX). Financial ratios such as Return on Assets (ROA), Return on Equity (ROE), Earnings Per Share (EPS), and Price to Book Value (PBV) are used as indicators of financial performance. Data were obtained from the 2023 financial reports of technology sector companies. The analysis was conducted using linear regression and tests of validity and reliability of the instruments. The results show that EPS has a significant influence on market value. This indicates that earnings per share is one of the main factors considered by investors when determining the market value of a company's stock, especially in the technology sector, which is characterized by high dynamics and rapid development. Furthermore, the findings also suggest that although other ratios such as ROA, ROE, and PBV are commonly used to assess financial performance, in the context of the technology sector, their influence on market value is not as strong as EPS. The technology sector, which relies on innovation and product development, makes EPS the most relevant benchmark for investors as it reflects the company's ability to generate sustainable net profits. Therefore, this study provides an important contribution to financial managers and investors by encouraging greater focus on managing and improving EPS as a strategy to enhance a company's market value on the Indonesia Stock Exchange. Thus, a deeper understanding of the relationship between financial performance and market value can support more effective investment decisions and financial management in the technology sector.